Pemanfaatan Limbah Anorganik untuk Revitalisasi Kebun Toga dan Gizi di Desa Kebumen - Stanislaus, Sugiyarta; Diasmika Ardhy, Handy; Kirana, Diva; Gilang Exfanto, Tanjung; Sapitri, Tiana (Jurnal Bina Desa, 2024)
Kebumen Village, Banyubiru District, Semarang Regency faces challenges in managing inorganic waste, particularly plastic, and the need to enhance the use of medicinal plants (TOGA) for community health. The program "Utilization of Inorganic Waste for Revitalizing TOGA Gardens and Nutrition in Kebumen Village" aims to educate the community about plastic waste management and revitalizing TOGA gardens to support village nutrition and economy. The methods used include field surveys to identify garden deficiencies, designing and collecting materials such as used plastic bottles, and implementing activities to create plant pots and decorative elements from plastic waste. This process involves the community at every stage, from preparation to applying plant pots in the TOGA garden. The results show that utilizing plastic waste effectively reduces environmental impact and improves the aesthetics and functionality of the garden. The program successfully raised community awareness about recycling and waste utilization, and strengthened food security and health through TOGA planting, providing sustainable benefits for Kebumen Village.